(untitled) - Kuo, Benjamin C. (Englewood Cliffs, 1995)
This book has a total of 188 illustrative examples. Some of these are simple, for the purpose of illustrating new ideas and subject matter. Some examples are quite elaborate, in order to bring the pratical World closer to you. Furthermore, the objective of this book is to present to complex subject in a clear and thorough way.
Keywords: Automatic control